المناخ المدرسي وعلاقته باكتساب القيم الديمقراطية لدى تلاميذ المرحلة الثانوية "دراسة ميدانية بثانويات مدينة بوسعادة " - نعيمة قذيفة (University of M'Sila, 2024)
تادف الد ا رسة إلى الوشف ع الع قة بي المناخ المدرسي واكتساب القيم الديمق ا رطية لت ميذ المرحلة ال انوية ، و قا خرعار ومؤ ا رس ع م متغيرل الد ا رسة. ولتحقيق زذدا اا تم استخدا المناج الوةفي وتربيق استمار الا ستبيا على عينة م ت ميذ سنة ال ة انول ب انوياس مدينة بوسعار والتي قدرس ب خ 293 تلميذ وتلميذ . وذلك رعد التحقق م ةدقاا و ؤاتاا وعليه شفت نتائج الد ا رسة ع تحقق الفرمية العامة التي ترب زنه " ت وجد ع قة ارتؤاطية ذاس رلالة إحلاائية بي ." α≤ المناخ المدرسي واكتساب القيم الديمق ا رطية لدب ت ميذ السنة ال ة انول عند مستوب معنوية خ 0.05 وتعسيسا على ذلك تحققت الفرمية الجزئية اخولى التي تنص على زنه: "توجد ع قة ارتؤاطية ذاس رلالة إحلاائية بي المناخ العائلي واكتساب قيم الحوار لدب وتحققت الفرمية الجزئية ال انية التي تنص على زنه" توجد ع قة ارتؤاطية ذاس رلالة إحلاائية بي المناخ " α≤ ت ميذ السنة ال ة انول عند مستوب معنوية خ 0.05 و ذلك تحقق الفرمية الجزئية ال ال ة زيض ا والتي تنص على زنه: "توجد " α≤ الذاتي واكتساب قيم الحرية لدب ت ميذ السنة ال ة انو ل عند مستوب معنوية خ 0.05 " α≤ ع قة ارتؤاطية ذاس رلالة إحلاائية بي المناخ الإنساني واكتساب قيم المسؤولية الاجتماعية لدب ت ميذ السنة ال ة انول عند مستوب معنوية خ 0.05 وبخلاول الفرمية ال ا ررعة: يمج الاستدلال عد تسجيع رو إحلاائية لتلاو ا رس المؤحو ي حول الع قة الارتؤاطية بي المناخ المدرسي واكتساب القيم الديمق ا رطية لدب ت ميذ سنة ال ة انول ت عزب خل متغير خلاي على عد ةحة قبول الفرمية. كما قدمت الد ا رسة مجموعة م ال مقترحاس التي ي مج ز ت ضيل م س ير الفعع التربول بتروير مناخ المؤسسة ال انوية ي مجال الإعدار الديمق ا رطي للنا ة.
The study aimed to unveil the relationship between school climate and the acquisition of democratic values for secondary school students, according to the dimensions and indicators of each of the study's variables. To achieve us these objectives, the descriptive approach was used to apply the questionnaires to administer a questionnaire to a sample of third-year secondary school students in high school in the city of Bou Saada, estimated at (293) male and female students. after verifying its validity and reliability. Accordingly, the results of the study revealed the fulfillment of the general hypothesis, which states that " there is a statistically significant correlation between the school climate and the acquisition of democratic values among third-year secondary school students at a significant level )α≤0.05 ( Based on this, the first partial hypothesis was fulfilled. "There is a statistically significant correlation between family climate and the acquisition of dialogue values among third- third-year secondary school students at a significant level )α≤0.05(The second partial hypothesis we fulfilled states: "Subjective climate has a relationship you mean correlation? with the acquisition of the values of freedom among -year third-year secondary school students at a level )α≤0.05(. The third partial hypothesis was abo also fulfilled, which states: "There is a statistically significant correlation between the humanitarian climate and the acquisition of social responsibility values among third-year secondary school students at the level of Significant )α≤0.05( ؛The study also presented a set of recommendations that could illuminate the you mean the course? of educational action by developing the climate of secondary school in the context of democratic preparation for young people.
Keywords: المناخ المدرسي _ القيم _ القيم الديمق ا رطية _ التلميذ _ المرحلة ال انوية .; School climate; values; democratic values; pupil; secondary education level.